2002
DOI: 10.1104/pp.001776
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Characterization of a Cold-Regulated PhosphoethanolamineN-Methyltransferase from Wheat

Abstract: A cDNA that encodes a methyltransferase (MT) was cloned from a cold-acclimated wheat (Triticum aestivum) cDNA library. Molecular analysis indicated that the enzyme WPEAMT (wheat phosphoethanolamine [P-EA] MT) is a bipartite protein with two separate sets of S-adenosyl-l-Met-binding domains, one close to the N-terminal end and the second close to the C-terminal end. The recombinant protein was found to catalyze the three sequential methylations of P-EA to form phosphocholine, a key precursor for the synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
71
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 43 publications
3
71
0
Order By: Relevance
“…Similarly, orcinol OMT was reported to carry out two sequential O-methylations in rose (Rosa 3 hybrida) scent biosynthesis (Lavid et al, 2002;Scalliet et al, 2002). Sequential methylation has also been reported for certain N-methyltransferases (Nuccio et al, 2000;Charron et al, 2002), but these proteins possess a different structural domain. In comparison, SOMT1 accepted both benzylisoquinoline and protoberberine substrates, showed no discrimination toward N-desmethyl or N-methylated BIAs, and was able to catalyze sequential O-methylations on both the isoquinoline and benzyl moieties.…”
Section: Benzylisoquinoline (Rs)-norlaudanosoline Was Not Accepted mentioning
confidence: 99%
“…Similarly, orcinol OMT was reported to carry out two sequential O-methylations in rose (Rosa 3 hybrida) scent biosynthesis (Lavid et al, 2002;Scalliet et al, 2002). Sequential methylation has also been reported for certain N-methyltransferases (Nuccio et al, 2000;Charron et al, 2002), but these proteins possess a different structural domain. In comparison, SOMT1 accepted both benzylisoquinoline and protoberberine substrates, showed no discrimination toward N-desmethyl or N-methylated BIAs, and was able to catalyze sequential O-methylations on both the isoquinoline and benzyl moieties.…”
Section: Benzylisoquinoline (Rs)-norlaudanosoline Was Not Accepted mentioning
confidence: 99%
“…These pathways allow for the use of exogenous choline and other phospholipids to be used for the synthesis of the major membrane phospholipid. In contrast, plants endogenously synthesize phosphocholine (pCho) 2 via the sequential methylation of phosphoethanolamine (pEA) in the phosphobase methylation pathway (3)(4)(5)(6)(7)(8). Interestingly, the plant-like phosphobase methylation pathway is also found in the free-living nematode Caenorhabditis elegans and the protozoan parasite Plasmodium falciparum, which causes malaria (9 -14).…”
mentioning
confidence: 99%
“…1A) (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Although the PMT found in plants, nematodes, and protozoans all catalyze the S-adenosylmethionine (AdoMet)-dependent methylation of pEA to pCho, the physical organization of the methyltransferase domains in these enzymes from plants (type 1), protozoa (type 2), and nematodes (type 3) differs dramatically (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PfPMT catalyzes the three-step S-adenosylmethionine methylation of phosphoethanolamine to form phosphocholine, which is used as a substrate by PfCCT and subsequently by PfCEPT to form PtdCho (2,12). The transmethylation of phosphoethanolamine to form phosphocholine also exists in plants, worms, and other protozoa but not in mammals (11,(13)(14)(15)(16). Recent genetic studies have shown that parasites lacking a functional SDPM pathway are severely altered in their development, produce half the number of nuclei and daughter parasites compared with wild-type P. falciparum, and show increased cell death (17).…”
mentioning
confidence: 99%